A simple index to quantify and compare the magnitude of intraspecific geographic plumage colour variation in typical antbirds (Aves: Passeriformes: Thamnophilidae). (9th April 2020) - Marcondes, Rafael S; Brumfield, Robb T
Abstract: Intraspecific geographic phenotypic variation is a crucial theme in evolutionary biology. Comparing its magnitude across species can provide insights into its ecological and genetic correlates. Here, we developed an index, which we dub the V index, to quantify intraspecific plumage colour variation in typical antbirds (Thamnophilidae), a family which has long interested ornithologists due to a high prevalence of intraspecific variation. The V index is based on a bivariate colour space defined by brightness and redness. Its value for each species equals the mean area occupied by each of its subspecies in that colour space, divided by the area of the species. Lower values indicate greater intraspecific geographic variation. Based on this index, Thamnophilus caerulescens (Variable Antshrike) was exceptionally geographically variable compared to other thamnophilids, as previously suggested based on qualitative evidence. In general, we found that the most variable species had disjunct distributions and deep phylogeographic structure, suggesting an effect of historical population dynamics in producing geographic variation. The V index can be adapted for use with other taxa, traits, and taxonomic levels, and we expect it will instigate novel ways of thinking about phenotypic variation in birds and other animals.